Leveraging the Interdependencies Between Barrier Islands and Backbarrier Saltmarshes to Enhance Resilience to Sea-Level Rise - Hein, Christopher J.; Fenster, Michael S.; Gedan, Keryn B.; Tabar, Jeff R.; Hein, Emily A.; DeMunda, Todd (Frontiers in Marine Science, 2021)
Barrier islands and their backbarrier saltmarshes have a reciprocal relationship: aeolian and storm processes transport sediment from the beaches and dunes to create and build marshes along the landward fringe of the island. In turn, these marshes exert a stabilizing influence on the barrier by widening the barrier system and forming a platform onto which the island migrates, consequently slowing landward barrier migration and inhibiting storm breaching. Here, we present a novel framework for applying these natural interdependencies to managing coastal systems and enhancing barrier-island resilience. Further, we detail application of these principles through a case study of the design of a marsh creation project that showcases the interdisciplinary engagement of scientists, engineers, stakeholders, and policymakers. Specifically, we describe: (1) the ecologic, sedimentologic, stratigraphic, and morphologic data obtained from the southern 4 km of Cedar Island (Virginia, United States) and nearby backbarrier tidal channels, tidal flats, and flood-tidal deltas, and (2) the use of those data to develop an engineering and design plan for the construction of a high (46 ha) and low (42 ha) fringing marsh platform located behind the island, proximal to a former ephemeral inlet. Additionally, we chronicle the process used to narrow five initial alternative designs to the optimal final plan. This process involved balancing best-available existing science and models, considering design and financial constraints, identifying stakeholder preferences, and maximizing restoration benefits of habitat provision and shoreline protection. Construction of this marsh would: (1) provide additional habitat and ecosystem benefits, (2) slow the rapid migration (up to 15 m/yr at present) of the barrier island, and (3) hinder island breaching. Ultimately, this project – presently at the final design and permitting stage – may enhance the storm and sea-level rise resilience of the island, backbarrier marshes and lagoons, and the mainland town community; and provide an example of a novel science-based approach to coastal resilience that could be applied to other global barrier settings.